John Wick. Chapter 4 [videorecording (Blu-Ray + DVD)] - Skarsgård, Bill (Lionsgate, 2023)
John Wick uncovers a trail to defeating The High Table. But before he can earn his freedom, Wick must face off against a new enemy with powerful associations across the globe and forces that turn old friends into foes.